Políticas públicas : proposta para o fortalecimento do ecossistema de inovação em Mato Grosso - Souza, Ângela Márcia de (2024)
This study aims to develop a set of proposals aimed at formulating public policies on Science, Technology and Innovation (ST&I) that promote the integration and strengthening of innovation ecosystems in Mato Grosso, with a focus on SECITECI's strategic actions. Using the inductive method, it is based on primary and secondary data obtained from SECITECI, as well as institutional and documentary records of local innovation ecosystems and the states best positioned in the State Competitiveness Ranking. Despite the significant advances resulting from the implementation of the Strategic ST&I Agenda for the State of Mato Grosso, drawn up in 2016 and valid until 2027, it is important to highlight that the state currently occupies 25th place in the State Competitiveness Ranking for the innovation pillar. This position highlights the challenges faced by the state in the area of innovation, reinforcing the need for effective public policies to boost the region's scientific and technological development. When considering the level of maturity of municipal innovation ecosystems in Mato Grosso, important challenges and opportunities are identified. It is essential to promote an environment conducive to the development of these ecosystems, ensuring greater integration between the various players and an effective incentive policy to stimulate innovation and entrepreneurship in all regions of the state.